2021
DOI: 10.3390/ijms22169029
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Digging into the Genetics of SMN Genes in the Therapeutic Scenario of Spinal Muscular Atrophy

Abstract: After 26 years of discovery of the determinant survival motor neuron 1 and the modifier survival motor neuron 2 genes (SMN1 and SMN2, respectively), three SMN-dependent specific therapies are already approved by FDA and EMA and, as a consequence, worldwide SMA patients are currently under clinical investigation and treatment. Bi-allelic pathogenic variants (mostly deletions) in SMN1 should be detected in SMA patients to confirm the disease. Determination of SMN2 copy number has been historically employed to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 85 publications
(150 reference statements)
1
18
0
2
Order By: Relevance
“…This is crucial in order to evaluate the effects of the approved therapies to unmask long-term benefits in treated patients. Given that not all discordant cases can be explained by this positive variant, it is necessary to further analyze the SMN2 region by NGS to detect other reported candidate variants [ 24 ] and the presence of hybrid SMN1-SMN2 structures [ 20 ], as well as to unravel novel phenotypic modifier variants. In the current therapeutic context, genetic studies in patients confirmed with biallelic SMN1 absence or pathogenic variants should consider not only testing for SMN2 copies but also investigating SMN2 variants and structures as part of the integral characterization of patients receiving expensive and sometimes lifelong therapies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is crucial in order to evaluate the effects of the approved therapies to unmask long-term benefits in treated patients. Given that not all discordant cases can be explained by this positive variant, it is necessary to further analyze the SMN2 region by NGS to detect other reported candidate variants [ 24 ] and the presence of hybrid SMN1-SMN2 structures [ 20 ], as well as to unravel novel phenotypic modifier variants. In the current therapeutic context, genetic studies in patients confirmed with biallelic SMN1 absence or pathogenic variants should consider not only testing for SMN2 copies but also investigating SMN2 variants and structures as part of the integral characterization of patients receiving expensive and sometimes lifelong therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Concretely, an inverse correlation between the number of SMN2 copies and the severity of the phenotype has been widely reported, given that the higher the number of SMN2 copies producing SMN functional protein, the milder the SMA phenotype [ 19 , 20 , 21 ]. Nevertheless, this correlation is not absolute, since discordant patients have been described in the literature, further classified as better-than-expected or worse-than-expected phenotypes according to their SMN2 copy number [ 19 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Verminderte NAIP-Kopienzahlen bzw. dessen Deletion scheinen mit einem früheren Erkrankungsalter und einem schweren Verlauf assoziiert zu sein 18 , 19 . Es wurden aber auch modifizierende Genveränderungen außerhalb des SMN-Lokus postuliert.…”
Section: Diskussionunclassified
“…In most cases, SMN2 copy number is inversely related to the clinical severity of SMA [1,4,6]. However, this correlation is not absolute [7], and some discordant genotype-phenotype correlations are observed [8].…”
Section: Introductionmentioning
confidence: 99%